Sarah Winnemucca - Zanjani, Sally Springmeyer, 1937-2018 (American Indian lives., 2001)
This book is the triumphant and moving story of Sarah Winnemucca (1844-91), one of the most influential and charismatic Native women in American history. Born into a legendary family of Paiute leaders in western Nevada, Sarah dedicated much of her life to working for her people. She played an instrumental and controversial role as interpreter and messenger for the U.S. Army during the Bannock War of 1878 and traveled to Washington in 1880 to obtain the release of her people from confinement on the Yakama Reservation. She toured the East Coast in the 1880s, tirelessly giving speeches about the plight of her people and heavily criticizing the reservation system. In 1883 she produced her autobiography-the first written by a Native woman-and founded a Native school whose educational practices were far ahead of its time. Sally Zanjani also reveals Sarah's notorious sharp tongue and wit, her love of performance, her string of failed relationships, and at the end, possible poisoning by a romantic rival.